Therapeutic Approaches in Pancreatic Cancer: Recent Updates - Lokender Kumar; Sanjay Kumar; Kumar Sandeep; Sanjay Kumar Singh Patel (Biomedicines, 2023)
Cancer is a significant challenge for effective treatment due to its complex mechanism, different progressing stages, and lack of adequate procedures for screening and identification. Pancreatic cancer is typically identified in its advanced progression phase with a low survival of ~5 years. Among cancers, pancreatic cancer is also considered a high mortality-causing casualty over other accidental or disease-based mortality, and it is ranked seventh among all mortality-associated cancers globally. Henceforth, developing diagnostic procedures for its early detection, understanding pancreatic cancer-linked mechanisms, and various therapeutic strategies are crucial. This review describes the recent development in pancreatic cancer progression, mechanisms, and therapeutic approaches, including molecular techniques and biomedicines for effectively treating cancer.